The Role of Preconceived Ideas in Macroeconomic Policy: Japan's Experiences in the Two Deflationary Periods - Koichi Hamada; Asahi Noguchi (Yale University, Economic Growth Center, 2005)
This paper examines the role of misleading economic ideas that most likely promoted the economic disasters of the two deflationary periods in Japanese economic history. Misleading ideas deepened the depression during the interwar years, and erroneous thinking prolonged the stagnation of the Japanese economy since the 1990s. While the current framework of political economy is based on the self-interests of political agents as well as of voters, we highlight the role of ideas in policy making, in particular, in the field of macro-economy where the incidence of a particular policy is not clear to the public. Using two significant examples, this paper illustrates the role of preconceived ideas, in contrast to economic interests, that dominantly influenced economic policy making.
Keywords: B2; F4; N2; 330; Preconceived ideas; perception on economic mechanism; vested interests; great depression; deflation in contemporary Japan; Wirtschaftspolitik; Entscheidung; Interessenpolitik; Ideologie; Deflation; Japan